Levantamento da realização do sujeito pronominal em entrevistas televisionadas: resultados iniciais - Silva, Mariana Frugeri (Universidade Federal de São Carlos, 2024)
This final paper aims to survey the number of occurrences and frequencies of expressed pronominal subject and null pronominal subject in texts of the television interview genre, produced in the year 2009. To achieve this, we present the phenomenon of the realization of the pronominal subject, based on studies that have already discussed it, considering it from the ideas of Chomsky (1981) and, above all, from the assumptions of the Theory of Linguistic Variation and Change (Weinreich; Labov; Herzog, 2006 [1968]). The initial results of this quantitative research point to the confirmation of the preference for the use of the expressed subject, more with the first and second persons of discourse than with the third. We hope with this work to contribute to the understanding of the phenomenon in Brazilian Portuguese, as well as to increase researchers' interest in the subject so that new investigations can be developed.
Analysis of the realization of pronominal subjects in televised interviews: initial results
Keywords: Sujeito pronominal nulo; Sujeito pronominal preenchido; Números de ocorrências; Frequências de uso; Gênero entrevista televisionada; Null pronominal subject; Expressed pronominal subject; Number of occurrences; Usage frequencie; Television interview genre; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA